Paediatric admissions and outcome in a general intensive care unit - Embu Henry; Yiltok Simon; Isamade Erdoo; Nuhu Samuel; Oyeniran Olushola; Uba Francis (Wolters Kluwer Medknow Publications, 2011)
Background: It is believed that intensive care greatly improves the prognosis for critically ill children and that critically ill children admitted to a dedicated Paediatric Intensive Care Unit (PICU) do better than those admitted to a general intensive care unit (ICU). Methods: A retrospective study of all paediatric (< 16 years) admissions to our general ICU from January 1994 to December 2007. Results: Out of a total of 1364 admissions, 302 (22.1%) were in the paediatric age group. Their age ranged from a few hours old to 15 years with a mean of 4.9 ± 2.5 years. The male: female ratio was 1.5:1. Postoperative admissions made up 51.7% of the admissions while trauma and burn made up 31.6% of admissions. Medical cases on the other hand constituted 11.6% of admissions. Of the 302 children admitted to the ICU, 193 were transferred from the ICU to other wards or in some cases other hospitals while 109 patients died giving a mortality rate of 36.1%. Mortality was significantly high in post-surgical paediatric patients and in patients with burn and tetanus. The length of stay (LOS) in the ICU ranged from less than one day to 56 days with a mean of 5.5 days. Conclusion: We found an increasing rate of paediatric admissions to our general ICU over the years. We also found a high mortality rate among paediatric patients admitted to our ICU. The poor outcome in paediatric patients managed in our ICU appears to be a reflection of the inadequacy of facilities. Better equipping our ICUs and improved man-power development would improve the outcome for our critically ill children. Hospitals in our region should also begin to look into the feasibility of establishing PICUs in order to further improve the standard of critical care for our children.